Inisiasi Pembentukan Sub-Klaster Kesehatan Reproduksi Dalam Upaya Kesiapsiagaan Krisis Kesehatan Di Jawa Tengah - Budi Raharjo, Bambang; Nugroho, Efa; Ainun Nisa, Alfiana; Istiada, Ayu (JUKEJ : Jurnal Kesehatan Jompa, 2025)
Central Java Province is one of the regions in Indonesia with a high disaster risk. This situation directly affects the disruption of health services, including reproductive health, which is crucial for vulnerable groups such as pregnant women, infants, and adolescent girls. Reproductive health services in crisis situations still face various challenges, such as limited interagency coordination, human resource constraints, and lack of service system integration. This study aims to explore the opportunities and challenges of forming a reproductive health sub-cluster as part of a health crisis preparedness strategy in Central Java. The method used is a qualitative descriptive approach involving cross-sector stakeholders such as the Health Office, BKKBN, BPBD, Community Health Centers (Puskesmas), community organizations, and universities. Activities were carried out through several stages: regional identification, coordination team formation, Minimum Initial Service Package (MISP) training, and sub-cluster implementation evaluation. The results showed the establishment of a sub-cluster structure that was able to strengthen coordination systems and improve stakeholder capacity in crisis response. The MISP workshop significantly increased participants’ understanding of reproductive health services in emergency situations. Focus group discussions also indicated increased cross-sector collaboration and community engagement.Therefore, the formation of the reproductive health sub-cluster is an effective strategy in building a responsive and inclusive preparedness system in disaster-prone areas. This model can be replicated in other regions to strengthen the resilience of the national health system.